SURGICAL TREATMENT OF INGUINAL HERNIA COMBINED WITH CRYPTORCHIDISM - M.KH. MALIKOV; F.M. KHAMIDOV; F.B. BOKIEV; O.M. KHUDOYDODOV; I.T. KHOMIDOV; N.A. MAKHMADKULOVA (Паёми Сино, 2022)
Objective: To evaluate outcomes of single-stage surgery performed for inguinal hernia combined with cryptorchidism.